Implementasi Pendekatan Matematika Realistik Pada Materi Teorema Pythagoras Di SMP Negeri 2 Medan - Wafiq Azizah Br. Sinaga; Kairuddin Kairuddin (Lembaga Pengembangan Kinerja Dosen, 2023)
The implementation of a realistic mathematical approach to learning the material of Pythagoras's theorem is carried out to encourage students to understand the material through everyday life so that the problems in the classroom gradually end in the secondary school. A realistic mathematical approach is an approach to learning mathematics that involves students to be more active by discussing in solving a problem or issue by connecting to daily life. The subjects in this study were 32 students of class VIII-3 SMP Negeri 2 Medan. This research is a Class Action Research (PTK) consisting of 2 cycles, with each cycle consisting from 2 meetings. after learning on cycle II by performing improvements from cycle I. Improvement is the planning of the student activity sheet that emphasizes the solution of issues with steps or indicators of problem-solving ability, because there are still many students who are not accustomed to the steps to solve problems. As for other improvements, namely planning activities in real life, in the 2nd cycle students solve the real problems of everyday life that students do. The researchers also provide motivation and reinforcement in learning to students to be active in group discussions and presentation of group work results to other groups, so that the interest of students in learning mathematics increases.